Multiple Sclerosis: LIFNano-CD4 for Trojan Horse Delivery of the Neuro-Protective Biologic “LIF” Into the Brain: Preclinical Proof of Concept - Flor, Raul de la; Robertson, Janette; Shevchenko, Rostislav V.; Alavijeh, Mo; Bickerton, Sean; Fahmy, Tarek; Metcalfe, Su M. (Frontiers in Medical Technology, 2021)
Multiple sclerosis (MS) is a demyelinating autoimmune disease that attacks the brain, with year-on-year loss of brain volume, starting late teens and becoming manifest late twenties. There is no cure, and current therapies are immunosuppressive only. LIF is a vital stem cell growth factor active throughout life—and essential for health of the central nervous system (CNS), being tolerogenic, myelinogenic, and neuroprotective. Nano-formulation of LIF (LIFNano) using FDA-approved PLGA captures LIF's compound therapeutic properties, increasing potency 1,000-fold when targeted to CD4 (LIFNano-CD4). Moreover, circulating CD4+ lymphocytes are themselves regulated by LIF to express the Treg phenotype, known to release T cell-derived LIF upon engagement with cognate antigen, perpetuating antigen-specific self-tolerance. With the longer-term aim of treating inflammatory lesions of MS, we asked, does LIFNano-CD4 cross the blood–brain barrier (BBB)? We measure pK and pD using novel methodologies, demonstrate crossing of the BBB, show LIF-cargo-specific anti-inflammatory efficacy in the frontal cortex of the brain, and show safety of intravenous delivery of LIFNano-CD4 at doses known to provide efficacious concentrations of LIF cargo behind the BBB.